William Golding’s Lord of the Flies: A Reconsideration (Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
This paper reconsiders William Golding’s Lord of the Flies. Allegorical writings can illustrate ethical, social or psychological and moral issues using the manipulation of images that have stipulated meanings other than their meanings as imitations of the actual world. Allegory has been used widely throughout history in all forms of art, and comprehensible for the reader, conveys hidden meanings through symbolic figures. Lord of the Flies had been written in relation to historical circumstances of the twentieth-century and to the personal experience of William Golding. Also, it has provided a critical analysis of the novel that treated the prominent perspective and elements in it. The novel is a parallel of life in the late twentieth century, while it looks like society a stage of enhancement in technology whereas, human morality is not completely mature yet. “Lord of the Flies is an allegorical microcosm of the world. The destruction of World War II because of the dictators who initiated this war has a profound impact on William Golding himself”. In the beginning, the paper gives an introduction to Golding’s point of view on humanity with the title of how to draw attention to me through allegory and fable, two forms of imaginative literature that encouraged the reader and listener to look for hidden meanings. Then it deals with William Golding’s Lord of the Flies from the cultural approaches of that time, who is one of the most prominent literary men of postmodernism that was famous for utilizing symbolism within the novel; “he used different kinds of symbols, characters, objects, animals, colors and setting to convey his message about his main theme”, in the last section we analyzed the postmodern features in Lord of the Flies and how they are used to depict Golding’s view. The way Golding uses allegory strengthens the symbolism of his novel. Finally, it tackles the educational value through his experiences in teaching along with critical analysis of Golding’s technique.